2009
DOI: 10.1016/j.jim.2009.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Single-pass, closed-system rapid expansion of lymphocyte cultures for adoptive cell therapy

Abstract: Adoptive cell therapy (ACT) for metastatic melanoma involves the ex vivo expansion and re-infusion of tumor infiltrating lymphocytes (TIL) obtained from resected specimens. With an overall objective response rate of fifty-six percent, this T-cell immunotherapy provides an appealing alternative to other therapies, including conventional therapies with lower response rates. However, there are significant regulatory and logistical concerns associated with the ex vivo activation and large scale expansion of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 16 publications
1
50
0
Order By: Relevance
“…One possibility is changing the culture technology used in the REP (using bioreactors or other large-scale systems), but this is unlikely to affect the resulting phenotype of the TILs after rapid expansion due to the fact that, ultimately, cell division is the major factor driving further T cell differentiation and the phenotypic changes observed. In fact, a recent study with melanoma TILs rapidly expanded with anti-CD3 and IL-2 in a new closed continuous perfusion bioreactor system versus the traditional REP, used by us in this study as well, found no significant difference in the resulting TIL phenotype in terms of the expression of CD28, CD27, and other major phenotypic markers of T cell differentiation (41).…”
Section: Discussionmentioning
confidence: 50%
“…One possibility is changing the culture technology used in the REP (using bioreactors or other large-scale systems), but this is unlikely to affect the resulting phenotype of the TILs after rapid expansion due to the fact that, ultimately, cell division is the major factor driving further T cell differentiation and the phenotypic changes observed. In fact, a recent study with melanoma TILs rapidly expanded with anti-CD3 and IL-2 in a new closed continuous perfusion bioreactor system versus the traditional REP, used by us in this study as well, found no significant difference in the resulting TIL phenotype in terms of the expression of CD28, CD27, and other major phenotypic markers of T cell differentiation (41).…”
Section: Discussionmentioning
confidence: 50%
“…The resulting tumor fragments were cultured in IMDM complete medium supplemented with 1800 U/mL IL-2 for 15 days, where half of the media was replaced after the first five days, and every three days thereafter as previously described [5]. The anti-gp100 HLA-A2-restricted T cell clone (directed against a gp100-derived peptide 209-217 in complex with HLA-A*02, and specifically targeting cancer cell lines SK23-mel and 624-mel) (a kind gift of Mark Dudley; Surgery branch, NCI, NIH), was grown using a REP as previously described [30][31][32]. Briefly, irradiated (5,000 rads) feeder cells (2.5x10 7 ) and anti-gp100 T cells (5x10 5 ) were cultured in Aim-V, 7.5% AB medium; composed of Aim-V (Invitrogen) supplemented with 7.5% decomplemented human AB serum (Sigma), and 2 mM Lglutamine, 100 U/mL penicillin, 100 g/mL streptomycin, 10 g/mL gentamicin (Wisent), 0.5 mg/mL anti-CD3…”
Section: Cell Cultures and Conditionsmentioning
confidence: 99%
“…To date, one of the most successful forms of immunotherapy incorporates adoptive transfer of autologous T lymphocytes after a lymphodepleting preconditioning regimen (10). However, this type of therapy is limited by the ability to generate tumor-reactive T cells and by the technical and financial resources required (11). An important variant involves the genetic modification of patient's peripheral blood lymphocytes (PBL) to express T-cell receptors (TCR) targeting melanocyte differentiation antigens (MDA) for use in adoptive transfer.…”
Section: Introductionmentioning
confidence: 99%